PROBLEMS OF THE FINANCIAL RESULT ANALYSIS OF THE COMPANIES CONSOLIDATED GROUP IN THE INVESTMENT DEVELOPMENT CONDITIONS - M. Efimova (Publishing House of the State University of Management, 2018)
The analysis of the financial result of the companies consolidated group has considered. The interpretation of the «financial result» concept applied to the group of financial and organizational related enterprises has given. It has shown, that the main analysis problems are the relationships opacity within the group as well as the specificity of the individual companies accountability and their subsequent consolidation into the group's accountability. An example of the financial result analysis of the companies group operating in the conditions of the investment development program has given.